Hydrogel Retaining Toxin‐Absorbing Nanosponges for Local Treatment of Methicillin‐Resistant Staphylococcus aureus Infection. (30th April 2015) - Wang, Fei; Gao, Weiwei; Thamphiwatana, Soracha; Luk, Brian T.; Angsantikul, Pavimol; Zhang, Qiangzhe; Hu, Che‐Ming J.; Fang, Ronnie H.; Copp, Jonathan A.; Pornpattananangkul, Dissaya; Lu, Weiyue; Zhang, Liangfang
<x xml:space="preserve">Abstract</x> A hybrid nanomaterial integrating unique toxin‐absorbing nanosponges with hydrogel is developed for local antivirulence therapy against methicillin‐resistant Staphylococcus aureus (MRSA) infection. The hydrogel composition is optimized to retain toxin nanosponges after administration while not compromising toxin transport into the gel for neutralization. Mice treated with the nanosponge–hydrogel hybrid show markedly reduced MRSA skin lesion development.